Media literacy among Metro Manila youth a mixed-method analysis of the levels of media literacy of Metro manila youth as determined by their digital news consumption - Rubinas, Anne Celine A.
As the digital media landscape continues to develop, there is a need to inquire about whether or not consumers are efficiently making use of the various means of consuming media contents. In line with this, the study aimed to examine Metro Manila youth's levels of media literacy in terms of their consumption behaviors when it comes to news on digital media platforms. Given the multiple issues in the measurement of media literacy, as well as the lack of a measurement that fits the local context, the first task undertaken for this study was the development of a media literacy scale that addresses the abovementioned concerns. The design of this instrument was guided by the Five-Factor of Media Literacy, Levels of Participation Model, and Resource Theory of Participation. The instrumentation process followed Eristi and Erdem's (2017) prescribed nine-step approach to scale development. The 30-item scale covered the five dimensions of media literacy, namely, access, analysis, evaluation, communication, and participation. Item analysis generated an overall Cronbach's alpha value, q=0.948 for the scale. Using the instrument, a survey was conducted among a randomly selected sample of Metro manila youth aged 15 to 30 years in order to gain empirical data on the state of the youth's media literacy. In line with the data gathered from 384 respondents, it was found that a majority of youth had low levels of media literacy. Respondents scored low on all five factors of media literacy, and the greatest number of them could be classified as indifferent consumers, Specifically, the youth rarely take in socio-civic and political related news contents, and they rarely act in socio-civic and political spheres as well.